The lithuanian block of the ECSB multi-country model - Igor Vetlov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
This paper presents preliminary results of modelling the Lithuanian block of the ESCB Multi-Country Model, LT_MCM.The theoretical structure of the LT_MCM is in line with most current mainstream macro models, i.e. supply factors determine the long-run equilibrium, while output is demand determined in the short run. Starting with a brief overview of the common features and main building blocks of a typical MCM country model block, we report the preliminary results of estimation of the Lithuanian MCM block.To illustrate the main characteristics of the estimated model, some standard shocks are introduced in the model and the responses studied.Compared to other MCM country blocks, we find that the Lithuanian macro model is characterised by relatively large and rapid response to shocks.Model simulation reveals that, compared to domestic prices, GDP is more responsive to shocks in the short run, while investment on average is more volatile than private consumption.The latter findings are similar to those reported for other EU country macro models.
URN:NBN:fi:bof-201408072101
Keywords: E10; E13; C5; 330; Macro Model; Lithuania